Childhood eczema: a comparative analysis - Ahmed, Ijaz; Ansari, Mujeeb; Malick, Kashef (Journal of Pakistan Association of Dermatologists, 2017)
Introduction Dermatological disorders affect children of all ages. Eczema is a common problem, along with infections and infestations. This study was carried out to determine frequency of various types of childhood eczema in our community. Â Materials and methods The study comprises an audit ofÂ freshly registered cases of childhood eczema presenting in the outpatient department of BISD from 1st October 2001, till 31st March 2003, over a period of 18 months. A total of 1038 patients, of either sex, up to 15 years of age were included. There were 541 (52%) males and 497 (48%) females. All the clinically diagnosed cases were subclassified into: atopic dermatitis, pityriasis alba, seborrheic dermatitis, contact dermatitis, napkin dermatitis, xerotic eczema, infective eczema, pompholyx, nummular eczema, and lichen simplex chronicus. The patients were divided into three groups according to age; infancy, 1-5years and 5-15 years. Â Results Atopic dermatitis (26%) was the most common type seen followed by pityriasis alba (25%), seborrheic dermatitis (21%), contact dermatitis (7%), napkin dermatitis (7%), xerotic eczema (6%), infective eczema (4%), nummular eczema (1.5%), pompholyx (1.5%) and lichen simplex chronicus (1%). There were 445 (42.9%) infants, 283 (27.3%) in the 1-5 years group and 309 (29.8%) in 5-15 years group. Atopic eczema (44%), seborrheic dermatitis (65%), napkin dermatitis (88%) and xerotic eczema (51%) were the most common in infancy. In the 1-5 year group, infective eczema (55%), atopic dermatitis (31%), pityriasis alba (28%) and contact dermatitis (23%) were seen commonly. In the 5-15year group, pityriasis alba (51%), contact dermatitis (47%), xerotic eczema (29.5%) and atopic dermatitis (24%) had the highest frequencies. Â Conclusion The clinical patterns of childhood eczema in our population are the same with some variations in frequency. Most of the patients present within the first 5 years of life. Â